PERAN PENDIDIKAN KARAKTER DALAM KELUARGA SEBAGAI UPAYA PEMBENTUKAN KECERDASAN SPIRITUAL ANAK - Choiri, Moh. Miftahul (Discovery, 2017)
This article aims to identify the role of moral education in the family as aneffort to form the spiritual intelligence of children. Lately the spotlight on morals is quiteserious in other words the quality of morality is still far from expectations. The quality ofmorality should always be strived to be better again. The family as the first and maineducational environment is a solid foundation in the process of moral formation. Moralformation requires early habituation because morals can not be formed in a short time.The existence of the role of education, especially family education will be very helpful inthe formation of the main person. The family is one of the institutions that are responsiblefor the implementation of education that will determine the success or failure of children'seducation. Therefore, parents in Islam have an obligation to provide education andguidance to their children as one of the mandate of Allah SWT. Children are in need ofeducation from their parents, so that he grows and develops into a child who has goodcharacter, and has a good spiritual intelligence.Keywords: Pendidikan karakter, keluarga, kecerdasan spiritual.